Relationship between components of metabolic syndrome and arterial stiffness in Chinese hypertensives - Jin Gong; Qunfang Xie; Ying Han; Bingying Chen; Lieyou Li; Guoxiang Zhou; Tingjun Wang; Liangdi Xie (Clinical and Experimental Hypertension, 2020)
Background: Subjects with metabolic syndrome showed increased risk of cardiovascular events. We investigated the relationship between components of metabolic syndrome and arterial stiffness in Chinese hypertensives. Method: 680 subjects (aged 58.44 ± 11.67 years, male 63.53%, hypertension 65.00%) were divided into five groups based on the number of known components of metabolic syndrome (MSCs) according to the criteria of 2010 Chinses Guidelines for Prevention and Management of Hypertension (0MSCs: n= 86; 1MSCs: n= 153; 2MSCs: n= 201; 3MSCs: n= 148; 4/5MSCs: n= 92.). Body weight, height, waist circumference, blood pressure and clinical biochemical tests were measured. Carotid-femoral pulse wave velocity (cfPWV) was measured using a non-invasive automatic device (Complior Analysis, France). Results: The level of cfPWV was significantly increased with the increasing number of MSCs (8.20 ± 1.54 vs 8.72 ± 1.48 vs 9.34 ± 1.77 vs 9.64 ± 1.86 vs 9.91 ± 2.19 m/s, P<0.05). In subjects with hypertension (n= 442), cfPWV was higher than those without hypertension (n= 238) (9.59 ± 1.90 vs 8.49 ± 1.50 m/s, P<0.05) . Stepwise multiple regression analysis revealed that age, gender, the number of MSCs, heart rate as well as serum uric acid level were determinants for cfPWV (P<0.05). In the subgroups stratified by age, systolic blood pressure correlated with cfPWV in hypertensives under 55 years old, while in non-hypertensives the correlation was found after 60 years old. Conclusion: The arterial stiffness became significant with the increasing of the metabolic components numbers, which was independent of age, gender and blood pressure. And the presence of hypertension played the most important role in the progress of arterial stiffness even compared with age.